EFFECTIVENESS OF INTERACTIVE MULTIMEDIA BASED ON ISPRING SUITE 9 METAMORPHOSIS MATERIAL ON STRENGTHENING INDEPENDENT CHARACTER OF ELEMENTARY SCHOOL STUDENTS - Shofiani, Reghina Rizky; Utama, Candra; Winahyu, Sri Estu (Universitas Negeri Malang, 2024)
The study was conducted to test the effectiveness of interactive multimedia based on ispring suite 9 on students' independent character. The research design was one group pretest-posttest conducted on one group only by providing a pre-questionnaire and post-questionnaire of independent character. The population used was 33 students with a saturated sampling technique. The variables in the study were the use of interactive multimedia ispring suite 9 as the independent variable and students' independent character as the dependent variable. The results of the effectiveness test using the Paired Samples t-Test with a sig. value. (2-tailed) of 0.000